0076 Long-term nightshift work and breast cancer risk in Hong Kong women: results update. (23rd June 2014) - Tsc, Lap Ah (Shelly); Wang, Feng; Chan, Wing Cheong; Wu, Çherry; Li, Mengjie; Kwok, Chi Hei; Leung, Siu Lan; Yu, Wai Cho; Yu, Ignatius Tak-sun
Abstract : Objectives: To report updated results on long-term nightshift work and breast cancer risk in Hong Kong women. Method: This ongoing case-control study involves three hospitals in Hong Kong. By 31/03/2013, we've consecutively recruited 443 newly diagnosed breast cancer cases and 335 age-matched controls from the hospital that the cases came from, with a response rate of 90%. We expect to collect 1000 cases and 1000 controls by 31/12/2013. We obtained each participant's lifetime occupational history and shift work, exposure to light-at-night and other important risk factors including family cancer history. We performed unconditional logistic regression analyses to calculate odds ratio (OR) after adjusting for potential confounders. Results: The age at diagnosis (interview) between cases and controls is comparable (55.1 ± 11.9 vs. 54.2 ± 14.6 years). More cases than controls were non-parity and non-breast feeding, but gave first birth slightly late. A significantly elevated (adjusted OR=1.90, 95% CI: 1.24–2.89) breast cancer risk was observed in never employed women. Among those ever employed, 19.8% of breast cancers had ever worked at nightshift at least once per month for ≥1 year and it was 21.7% for the controls. Further analyses revealed that nightshift work for ≥15 years resulted in an adjusted OR of 1.55 (95% CI: 0.76–3.14) but power is limited. There is no excess breast cancer risk for women with nightshift work for <15 years. Conclusions: This ongoing study provides supportive evidence on a positive association between long-term nightshift work and breast cancer risk. [Research Grants Council (Project no.: 474811) and Direct Grant (Project no.: 2041788), shelly@cuhk.edu.hk].